The association between liver function tests abnormalities and type 2 diabetes mellitus patients in Saudi Arabia: a cross-sectional study - Mehyar, Nimer; Alhajeri, Ziyad; Alosaimi, Muath; Alanazi, Ziyad; Alanazi, Abdulkarim; Abusaris, Raghib (Frontiers in Clinical Diabetes and Healthcare, 2025)
IntroductionIncreasing evidence shows that hyperglycemia-induced glucotoxicity and lipotoxicity that usually accompany diabetes development damage the endoplasmic reticulum and mitochondria of the hepatocytes in diabetic patients. Clinical studies highlighted the association between type 2 diabetes mellitus, comorbidities, and medications with liver function. The objective of this study is to explore the association between liver function tests’ abnormalities and comorbidities, medications, and other risk factors in type 2 diabetes patients registered in the Best-Care system of the Saudi Ministry of National Guard-Health Affairs.MethodsThis is a cross-sectional study employing a chart of patients diagnosed with type 2 diabetes mellitus. We drew a simple random sample of 523 T2DM patients who had a liver function test from the Best-Care database of the Ministry. We applied various statistical analyses, including Student’s independent t-test, Pearson’s chi-squared test, Fisher’s exact test, and odd ratios, to measure associations between different variables and liver function tests’ abnormalities.ResultsAbout 35% of patients included in this study showed an abnormal level of gamma-glutamyl transferase and prothrombin time. Abnormalities of serum albumin, prothrombin time, and total serum protein tests were significantly associated with age (P < 0.05). Gamma-glutamyl transferase test abnormalities were significantly associated with gender (P < 0.05). The study found associations between several comorbidities and the abnormalities of liver function tests. These tests include the total bilirubin, albumin, total serum protein, gamma-glutamyl trans, international normalized ratio, and alanine aminotransferase. The associations were at significant levels (P < 0.05). Liraglutide was significantly associated with aspartate aminotransferase (OR = 14.40, 95% CI = 2.8, 73.2), while allopurinol was significantly associated with international normalized ratios (OR = 24.67, 95% CI = 2.95, 206.58) and total serum protein (OR = 5.44, 95% CI = 1.43, 20.83).DiscussionThis study is the first to examine the association between type 2 diabetes mellitus and liver function tests’ abnormalities in Saudi Arabia. Although the results have a limited generalizability due to inherent biases, the findings align with similar studies in other populations. The study stresses the need to monitor liver functions, especially of T2DM patients who suffer from other conditions.